2006
DOI: 10.1111/j.1556-4029.2006.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Accuracy and Precision of Cranial Morphological Traits for Sex Determination

Abstract: Sex determination is a key analysis that forensic anthropologists perform in order to construct a biological profile of human remains. The techniques used in forensic investigations must meet the Mohan or Daubert criteria, for admissibility in a court of law. In this study, the precision and accuracy of 21 morphological characteristics of the skull were tested on a modern sample of 50 adult crania of European White ancestry. The following craniofacial features are identified as high-quality traits, defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
165
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(199 citation statements)
references
References 8 publications
6
165
2
7
Order By: Relevance
“…Forensic anthropologists are continually attempting to improve methods of skeletal identification through development of new methods of determining sex or fine-tuning of existing methods on various parts of the skeleton so that it can be admissible in court [e.g., 29,30]. The aim of this paper was to follow in this tradition, by developing population specific formulae that could be used on people living in Greece and the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Forensic anthropologists are continually attempting to improve methods of skeletal identification through development of new methods of determining sex or fine-tuning of existing methods on various parts of the skeleton so that it can be admissible in court [e.g., 29,30]. The aim of this paper was to follow in this tradition, by developing population specific formulae that could be used on people living in Greece and the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, various studies 2,3,4,5 have demonstrated that several anatomic landmarks of the skull and mandible can be used and that some of these landmarks typically present increased precision in identifying an individual compared with other. 3 Furthermore, the mandible is one of the most preserved bones in hominid and hominoid fossil records, 6 making it relevant to anthropological studies.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…3 Furthermore, the mandible is one of the most preserved bones in hominid and hominoid fossil records, 6 making it relevant to anthropological studies.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,14 The cephalometric variables used in the present study were considered based on the evidences of previous studies that have reported high accuracy in determination of sex using a discrete number of morphological features of the cranium. 7,10,14,16 It has been reported that the skeletal characteristics are age-related phenomena which appear or become pronounced at puberty and many are affected by senility. 3,5 Hence, in the present study the lower limit of the age was set at 25 years, as the craniofacial growth is complete by this age, and the upper limit of the age was laid down at 55 years.…”
Section: Discussionmentioning
confidence: 99%